Direct N-Alkylation of Aromatic Amines Using a Microflow Reactor: Enhancement of Selectivity and Reactivity - Choi, Yong-Sung; Kim, Yoon-Jung; Shen, Liu-Lan; Lee, Yong Sup; Jeong, Jin-Hyun (Synlett, 2015)
A simple and highly atom-economical method for the direct N-alkylation of aromatic amines by using a microflow reactor was developed to overcome the problem of over-alkylation. In the developed method, high-yield conversion (up to 100%) was achieved in a relatively short reaction time. The ratio of mono- to di-benzylated products (3.57:1) was higher than that achieved with batch reactions conducted in a 1 L scale flask (0.87:1). The structural features of the microflow reactor meant that short-chain alkyl halides could be converted into products with high reactivity and selectivity under superheating conditions, although their boiling point was much lower than the reaction temperature. This method was successfully applied to the synthesis of a range of secondary amines including an intermediate of indobufen synthesis.
Keywords: microflow reactors; aromatic amines; secondary amines; N-alkylation; over-alkylation